Condições de saúde bucal e acompanhamento odontológico de crianças portadoras de leucemia linfocítica aguda - Denise Siqueira Lobao (2006)
Purpose: To evaluate the conditions of the oral cavity of children with the diagnosis of acute lymphocytic leukemia (ALL) and the current oral complications of the chemotherapic treatment; to verify whether the introduction of the dental attendance during the treatment promotes an improvement of the oral health of those patients. Methods: Were included in this study children with age between 2 and 14 years, with diagnosis of ALL, escorted at the Hospital of Clinics (Hospital das Clinicas) - UFMG in the period of 2004 to 2005. The dental treatment consisted of initial evaluation and urgency, behavioral adjustment and adaptation of the oral environment, restorative treatment and preventive maintenance.Results: Of the total of 31 patient, seventeen (54,8%) were male. The mean age at the initial dental exam was six years. Eleven children (35,5%) lived in Belo Horizonte. Twenty patients (64%) had not received any previous dental service before this study. The assistance periodvaried from 0.2 to 19.7 months (mean 11.1 months). At the initial dental evaluation, 21 (67.7%) patients had decay activity, being the average of CPOD = 2.5 and ceod = 2.2. Eighteen patients needed an invasive dental approach and 19 (61,3%) exhibited gingivitis. The average index of invasive needs (INI) was 4.4% and the median of 2.8% (variation,0%/median to 22.5%) and 13 patients had INI equal zero. No statistically significant correlations were observed between the variable initial INI (%) and the per capita income (p=0.424) and initial INI (%) and the caretaker's education (p=0.057). Statistically significant correlation and a direct relationship were observed among the variables INI (%) and to firstmeasure of the index of visible plaque (IPV) (r=0.39; p=0.030), INI (%) initial and to first measure of the index of gingival bleeding (ISG) (r=0.44; p=0.016). Eighteen patients (58%) had some type of lesion an the mucosa during the dental attendance. The diagnosed lesions, infrequency order, were: ulcers, labial herpes, mucositis, herpetic gingivostomatitis, candidiasis, angular cheilitis and varicella.In the final dental evaluation, 25 (80.6%) patients were without decay activity. Three patients needed an invasive dental approach and 13 (42%) exhibited gingivitis. The average of the index of invasive needs (INI) was 0.3% and median zero (variation, 0% to 4,3%) and 28 (90,3%) patients had INI equal zero. The measures of initial IPV and INI were significantlyhigher than the final ones (p<0.001, for both comparisons) Conclusion: The majority number of patients had not had any access to a previous dental treatment and showed an oral health compromised at the moment of admission in the study, in the point of view as for the dental decay disease as for the periodontal disease. The establishment of a dental service program during the chemotherapic treatment favored thebalance and maintenance of those children's oral health.